2005
DOI: 10.1103/physrevb.72.125401
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of Au(100)-hex reconstruction in an electrochemical environment

Abstract: Surface energies of Au͑100͒ p͑1 ϫ 1͒ and Au͑100͒-hex as modeled by a p͑1 ϫ 5͒ unit cell have been calculated as a function of surface charge by the density functional method. When the surface is neutral, the surface energy of Au͑100͒-hex is lower than that of Au͑100͒, consistent with the experimental observation that a Au͑100͒ surface has a hexagonal, instead of a square top layer. Calculations show that the surface energies of both systems increase when the surfaces are positively charged and there is a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 55 publications
4
21
0
Order By: Relevance
“…Figure 5 shows the relaxed structure of the Au(100)-hex(1 Â 5) model, [14,15] where each surface atom has a different subsurface configuration locally. About the relative positions of the top (111) layer above the second (100) layer, one row containing Au(1), Au(3), and Au (5) is located along the top or bridge sites (100) layer as indicated by a red dash line in Figure 6, which we call top row.…”
Section: Examination By Dft Calculations Co-au 2 Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the relaxed structure of the Au(100)-hex(1 Â 5) model, [14,15] where each surface atom has a different subsurface configuration locally. About the relative positions of the top (111) layer above the second (100) layer, one row containing Au(1), Au(3), and Au (5) is located along the top or bridge sites (100) layer as indicated by a red dash line in Figure 6, which we call top row.…”
Section: Examination By Dft Calculations Co-au 2 Clustermentioning
confidence: 99%
“…In addition to Au(111), Au(100), Au(711), and Au(321) surfaces, we performed firstprinciples density functional theory (DFT) calculations of CO adsorption on a Au(100)-hex structure using a model (1 Â 5) cell. [14,15] The Au(100)-hex surface consists of a top hexagonal layer like the (111) surface above the usual (100) layer stacking, and each surface atom has a locally varying subsurface configuration. As will be shown later, we have found that the CO adsorption energy is varied and dependent on the location of the surface, indicating that the CO adsorption energy on gold should greatly depend on the local configuration under or around the surface Au atom.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only few theoretical attempts have been made to better understand the potentialinduced changes of the surface structure, ranging from tight binding studies [14] over simple glue models [15] to embedded atom simulations [16][17][18] and ab initio density functional theory calculations [19,20]. Focusing mainly on evaluating the surface free energies of the reconstructed and unreconstructed surfaces, the presence of the electrode potential was either neglected or treated in terms of an externally applied electric field, or by manually charging the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate different approximations in the context of modeling electrochemical systems [Haftel and Rosen, 2003;Kitchin et al, 2004;Gunnarsson et al, 2004;Feng et al, 2005;Rossmeisl et al, 2006;Taylor et al, 2006;Jacob, 2007a, b], in the following, we shall discuss each term of (5.15) separately:…”
Section: Extended Ab Initio Atomistic Thermodynamicsmentioning
confidence: 99%
“…Regarding theoretical studies, different attempts have been made to model and understand the structure and properties of systems under electrochemical conditions. An overview can be found in the reviews of Schmickler [1996aSchmickler [ , 1999, Koper et al [2003], Koper [2004] and the papers of Nazmutdinov and Shapnik [1996], Halley et al [2000], Vassilev et al [2001], Haftel and Rosen [2003], Feng et al [2005], Kitchin et al [2004], Gunnarsson et al [2004], Taylor et al [2006], and Jacob [2007a, b] and references therein. In these different works, mainly experimental input, semi-empirical approaches, or rather simplified models, have been used.…”
mentioning
confidence: 99%